2018
DOI: 10.31339/2413-3329-2018-1(7)-240-244
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and pedagogical training of future teachers (on the example of Pavol Jozef Šafárik University in Košice, Slovak Republic)

Abstract: Науковий вісник Мукачівського державного університету, 2018 Серія «Педагогіка та психологія». Випуск 1 (7) companies and trade organizations in the process of professional development of future skilled workers. Nevertheless, the experience of the future skilled workers' vocational education and training in Liechtenstein is important not only for scientific analysis, but also for implementation in the national educational system. The proven system of cooperation with neighboring countries using their scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Authors in the article [22] deals with the problem of professional training of future teachers in Pavol Jozef Šafárik University in Košice (Slovak Republic). The authors found that the psychological and pedagogical component of the content is half the total volume of training.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Authors in the article [22] deals with the problem of professional training of future teachers in Pavol Jozef Šafárik University in Košice (Slovak Republic). The authors found that the psychological and pedagogical component of the content is half the total volume of training.…”
Section: Analysis and Discussionmentioning
confidence: 99%